Diagnostic Accuracy of Computed Tomography in the Diagnosis of Fungal Sinusitis Keeping Histopathology as A Gold Standard - Bushra, .; Aman, Nasreen (Biological and Clinical Sciences Research Journal, 2025)
Fungal sinusitis is an increasingly recognized cause of chronic sinonasal disease, particularly in immunocompromised and diabetic patients. Early and accurate diagnosis is essential for appropriate surgical and medical management. Computed tomography (CT) of the paranasal sinuses is widely used for initial evaluation; however, its diagnostic performance must be validated against histopathology, which remains the gold standard. Objective: To determine the diagnostic accuracy of computed tomography (CT) in diagnosing fungal sinusitis, using histopathological findings as the gold standard. Methods: This cross-sectional validation study included 143 patients aged 18–65 years presenting with clinical suspicion of fungal sinusitis. Patients with sinonasal tumors, antrochoanal polyps, and pregnant or lactating women were excluded from the Radiology Department, Lady Reading Hospital, Peshawar. The study duration was from 25-10-2024 to 25-04-2025. All participants underwent CT scanning of the paranasal sinuses followed by surgical intervention and histopathological examination. Diagnostic accuracy parameters, including sensitivity, specificity, and overall accuracy, were calculated using a 2×2 contingency table. Data analysis was performed using SPSS version 25. Results: The mean age of the patients was 42.75 + 14.689 years, there were 93 (65%) male patients. CT scan showed fungal sinusitis positive in 88 patients (61.5%), while histopathology in 75 patients (52.4%). Diagnostic accuracy of CT scan for fungal sinusitis was 85.31%, with sensitivity 94.67% and specificity 75%, respectively. Conclusion: Computed tomography is an effective and reliable imaging modality for diagnosing fungal sinusitis, demonstrating high sensitivity and good diagnostic accuracy compared with histopathology. CT scanning is a valuable noninvasive diagnostic tool for early detection and preoperative assessment of fungal sinusitis.